(untitled) (Fractal: Journal of Psychology, 2013)
This study aims to discuss the work of Eros and Thanatos in the context of social regulation, where the organizational social responsibility is commonly identified as being a management system capable of minimizing the negative effects of capitalism. The fieldwork indicated a fallacy between discourse and practices of responsibility. Qualitative data from three organizations were used and categorized based on the logic of social representations. It has been identified that the organizational social responsibility is in the service of Eros, being a possible way to beat the anguish of organizational death. However, that model is vulnerable to the work of Thanatos. It has been concluded that the perception of the work of death that is noticeable in the institutional dynamics may favor its confrontation and also find ways out to the necrosis in the social tissue which work organizations are also part.